Sodium Reduction in Bouillon: Targeting a Food Staple to Reduce Hypertension in Sub-saharan Africa - Archer, Nicholas S.; Cochet-Broch, Maeva; Mihnea, Mihaela; Garrido-Bañuelos, Gonzalo; Lopez-Sanchez, Patricia; Lundin, Leif; Frank, Damian (Frontiers in Nutrition, 2022)
Bouillon cubes are a staple ingredient used in Sub-Saharan African countries providing flavour enhancement to savoury foods. Bouillon has been identified as a vehicle for fortification to overcome micronutrient deficiencies in Sub-Saharan Africa. However, bouillon has a high sodium content (and in addition with other foods) contributes to dietary sodium intake above recommended guidelines. High dietary sodium intake is a key risk factor for hypertension and cardiovascular disease (CVD). Africa has the highest rates of hypertension and CVD globally with nearly half the adult population above 25 years affected. This review presents current state of research on sodium reduction strategies in bouillon. The key challenge is to reduce sodium levels while maintaining optimal flavour at the lowest possible production cost to ensure bouillon continues to be affordable in Sub-Saharan Africa. To produce lower sodium bouillon with acceptable flavour at low cost will likely involve multiple sodium reduction strategies; direct reduction in sodium, sodium replacement and saltiness boosting flavour technologies. Efforts to reduce the sodium content of bouillon in Sub-Saharan Africa is a worthwhile strategy to: (i) lower the overall sodium consumption across the population, and (ii) deliver population-wide health benefits in a region with high rates of hypertension and CVD.